A NEW JAVANESE SPECIES OF MARASMIUS (TRICHLOMATACEAE) - Atik - Retnowati (Research Center for Biology, 2008)
RETNOWATI, A. 2008. A new Javanese species of Marasmius (Tricholomataceae). Reinwardtia 12(4): 335 – 336.— Marasmius xenopellis is described as a new species based on material collected from Mt. Halimun National Park, West Java.